EVALUASI KEBIJAKAN PENGELOLAAN SAMPAH DI DINAS KEBERSIHAN DAN PERTANAMAN KOTA PALU - Rendy, Mohammad (Katalogis, 2015)
The objectives of the study are to find out and to analyze the evaluation of integrated waste management policy at Department of Hygiene and Horticulture of Palu City. The type of the study is qualitative research by taking purposively the implementer informant and target policy of Palu. Technique of data collection consisted of observation, interview and documentation. While technique of data analysis are data reduction, display data and taking conclution and verification. The result of study showed that the evaluation of integrated waste management policy has been implemented but not maximized yet because there were problems in the evaluation criteria such as effectiveness, efficiency and adequacy. Effectiveness has not been achieved due to lack of support and awareness in waste management. Efficiency has not been achieved because of the behavior and awareness of the environment is still low. Besides the operational time for waste disposal has not been fully obeyed. Whereas the criteria of adequacy has not been able to solve the problem in hygiene and environmental health because of garbage dump such as TPS, TPST pose a foul odor in the area. So, indirectly affect the hygiene and public health.